Penerapan Edukasi Dengan Media Booklet Dan Audiovisual Untuk Meningkatkan Pengetahuan Keluarga Tentang Perawatan Luka Kaki Diabetes Mellitus Di Wilayah Binaan Puskesmas Sekaran Semarang - Diana Dayaningsih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Knowledge about wound care in families and patients with diabetes mellitus foot wounds needs to be increased so that families can assist in the optimal wound healing process and patients can understand more about wound care. The need for education with booklets and audiovisual media for families of diabetes mellitus patients is to increase the effectiveness of family understanding in detecting signs of diabetes mellitus foot problems and appropriate treatment. The purpose of the case study is to illustrate the application of education using booklets and audiovisual media to increase family knowledge about the treatment of diabetic foot wounds in the Sekaran Health Center target area. This research method uses a case study with a descriptive approach. The results of the study regarding family knowledge about the treatment of diabetes mellitus foot wounds were obtained in subject I before receiving education a good level of knowledge with a score of 24, after receiving education a good level of knowledge with a score of 28, subject II before receiving education a moderate level of knowledge with a score of 19, after receiving education level of knowledge is good with a score of 26. Conclusion: health education is very important to increase family knowledge about the treatment of foot wounds with diabetes mellitus, carried out at the Sekaran Health Center.